ASPECTS OF PERSONALITY SELF-ACTUALIZATION IN THE CONTEXT OF LIFE QUALITY IN RELATION WITH SENSE OF HUMOR - Strazdiņa, Irina (European Scientific Journal, ESJ, 2014)
Diverse factors that determine life quality and aspects that higher or lower sense of life quality corresponding to the needs of individual are analyzed in the article. There is fortified necessity of appropriate self-nurturing corresponding to the most important competence of person, that includes the readiness of person for self-development and selforganization of own activities, acting, readiness to take responsibility for own life. Possibilities of personality self-actualization and meaning of sense of humor in the context of life quality.